2018
DOI: 10.1016/j.ttbdis.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen transmission in relation to duration of attachment by Ixodes scapularis ticks

Abstract: The blacklegged tick, Ixodes scapularis, is the primary vector to humans in the eastern United States of the deer tick virus lineage of Powassan virus (Powassan virus disease); the protozoan parasite Babesia microti (babesiosis); and multiple bacterial disease agents including Anaplasma phagocytophilum (anaplasmosis), Borrelia burgdorferi and Borrelia mayonii (Lyme disease), Borrelia miyamotoi (relapsing fever-like illness, named Borrelia miyamotoi disease), and Ehrlichia muris eauclairensis (a minor causative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 74 publications
1
112
0
1
Order By: Relevance
“…Several contrasting findings can however be observed according to the tick scale we are looking at. With sensitive detection tools, tick co-infections are usually observed in tick-borne pathogen analyses [8,29,39].…”
Section: The Organ Scalementioning
confidence: 99%
“…Several contrasting findings can however be observed according to the tick scale we are looking at. With sensitive detection tools, tick co-infections are usually observed in tick-borne pathogen analyses [8,29,39].…”
Section: The Organ Scalementioning
confidence: 99%
“…Overall, we documented infection, based on detection of B. miyamotoi DNA, in blood from 13 (57%) of 23 mice exposed to a single infected larva and from 5 (83%) of 6 mice exposed to two infected larvae feeding simultaneously. Increased probability of tick feeding to result in host infection after exposure to multiple versus single infected ticks was previously reported for nymphal I. scapularis ticks infected with the Lyme disease spirochetes, B. burgdorferi s.s. and B. mayonii (Eisen, 2018). In this study, all 18 PCR-positive mice also demonstrated seroreactivity to B. miyamotoi .…”
Section: Resultsmentioning
confidence: 99%
“…The primary vector of B. miyamotoi to humans in the eastern part of the United States is the blacklegged tick, Ixodes scapularis , which also transmits the Lyme disease spirochetes, Borrelia burgdorferi sensu stricto (s.s.) and Borrelia mayonii (Krause et al, 2015; Breuner et al, 2017; Eisen, 2018). For nymphal and adult I. scapularis ticks, local infection prevalence with the relapsing fever spirochete, B. miyamotoi , is commonly 10-fold lower than for the Lyme disease spirochete, B. burgdorferi s.s. (Tsao et al, 2004; Krause et al, 2015; Nelder et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A prospective study showed that 8% of people bitten by a B. burgdorferi infected tick acquired the infection [18]. However, it is well known that the risk steadily rises with the increasing duration of the blood meal, reaching 70% if the tick remains attached up to 72 h [19].…”
Section: Discussionmentioning
confidence: 99%